Grazing exclusion altered the effect of plant root diameter on decomposition rates in a semiarid grassland ecosystem, northeastern China. Issue 2 (5th February 2020) - Luo, Yongqing; Ding, Jieping; Zhao, Xueyong; Li, Yuqiang; Lian, Jie; Wang, Tao
Abstract: Root decomposition often decreases with increasing root diameter, but this relationship is affected by other factors, including the microclimate and land use. The mechanisms that underlie these interactions are unclear. We performed an Artemisia halodendron root decomposition litterbag experiment using fine (<2 mm), medium (2–5 mm) and coarse (>5 mm) roots. We used the same incubation duration (356 days) with five starting dates (May, June, July, October and September) in fenced (grazing exclusion) and grazed plots. Root samples installed in May decomposed faster than those installed in September, and roots decomposed faster in fenced plots than in grazed plots. Root decomposition was the highest for fine roots installed in any month, and medium roots decomposed faster than coarse roots with installation in all the months except May and July. Grazing exclusion and starting incubation time both interacted with root diameter. Root decomposition for a given diameter did not differ significantly between fenced and grazed plots; however, in both land uses, root decomposition decreased significantly with increasing root diameter. Microclimate, especially precipitation, differed among the starting dates, and precipitation patterns (especially in the first growing season) significantly ( p  < .01) affected coarse root decomposition in the fenced plots. In summary, root decomposition was significantly ( p  < .01) affected by root diameter. This effect was altered by grazing exclusion and by starting dates. These results highlight the importance of the starting date for root decomposition in a semiarid grassland, suggesting this date should be accounted for in future studies of root decomposition.